2021
DOI: 10.1177/23259671211037311
|View full text |Cite
|
Sign up to set email alerts
|

Operative Versus Nonoperative Management for Distal Biceps Brachii Tendon Lesions: A Systematic Review and Meta-analysis

Abstract: Background: Both nonoperative and operative treatments have been proposed to manage distal biceps brachii tendon avulsions. However, the advantages and disadvantages of these approaches have not been properly quantified. Purpose: To summarize the current literature on both nonoperative and operative approaches for distal biceps brachii tendon ruptures and to quantify results and limitations. The advantages and disadvantages of the different surgical strategies were investigated as well. Study Design: Systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 74 publications
0
6
0
1
Order By: Relevance
“…This is thought to be due to dissection of the supinator required by the 2-incision technique, resulting in increased postoperative fibrosis. 14 Initial studies demonstrated greater risk of nerve injury in the one incision technique; however, recent developments in fixation devices limit the need for extensive dissection of the cubital fossa and now demonstrate low level of transient nerve injury. 15 …”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is thought to be due to dissection of the supinator required by the 2-incision technique, resulting in increased postoperative fibrosis. 14 Initial studies demonstrated greater risk of nerve injury in the one incision technique; however, recent developments in fixation devices limit the need for extensive dissection of the cubital fossa and now demonstrate low level of transient nerve injury. 15 …”
Section: Discussion/conclusionmentioning
confidence: 99%
“…A recent meta-analysis demonstrated no significant difference in postoperative strength ratio to the uninjured limb with flexion and supination strength when comparing cortical buttons, suture anchors, and transosseous suture. 14 The use of a knotless suture anchor compared with an inlay intraosseous screw decreases radial neck fracture risk, as well as radial tuberosity osteolysis. 16 This has been related to the substantially sized bone tunnel required for interference screws, without significant clinical benefit.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Indeed, in a recent survey of shoulder surgeons in the United Kingdom, 83% of respondents reported repairing more than half of these injuries [ 8 ]. Systematic reviews and meta-analyses comparing non-operative versus operative management have suggested operative management to result in improved strength and better patient-reported outcomes [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Distal biceps ruptures occur after an eccentric load applied to the flexed elbow. Although surgical repair is most often advocated for restoration of flexion and supination strength, 1 in chronic cases or high energy mid-substance tears or in patients with substantial tendon degeneration, repair is not always possible. In these cases, reconstruction with either autograft or allograft tendon can be performed.…”
mentioning
confidence: 99%